Degradation and Toxicity Analysis of a Reactive Textile Diazo Dye-Direct Red 81 by Newly Isolated Bacillus sp. DMS2 - Amin, Shivani; Rastogi, Rajesh Prasad; Chaubey, Mukesh Ghanshyam; Jain, Kunal; Divecha, Jyoti; Desai, Chirayu; Madamwar, Datta (Frontiers in Microbiology, 2020)
An efficient diazo dye degrading bacterial strain, Bacillus sp. DMS2 was isolated from a long-term textile dye polluted environment. The strain was assessed for its innate ability to completely degrade and detoxify Direct Red 81 (DR81) textile dye under microaerophilic conditions. The degradation ability of strain showed significant results on optimizing the nutritional and environmental parameters. Based on statistical models, maximum efficiency of decolorization achieved within 24 h for 100 mg/l of dye supplemented with glucose (0.02 %), MgSO4 (0.002 %) and urea (0.5 %) at 30ºC and pH (7.0). Moreover, a significant catabolic induction of a laccase and azoreductase suggested its vital role in degrading DR81 into three distinct metabolites (intermediates) as by-products. Further, toxicity analysis of intermediates were performed using seeds of common edible plants, aquatic plant (phytotoxicity) and the nematode model (animal toxicity), which confirmed the non-toxic nature of intermediates. Thus, the inclusive study of DMS2 showed promising efficiency in bioremediation approach for treating industrial effluents.